Sprachhandlungskoordination in der Chat-Kommunikation - Beißwenger, Michael,Beiwenger, Michael,Beiawenger, Michael,Beisswenger Michael, ... (De Gruyter, 2007)
The book presents a fundamental study of the coordination of language action in chat communication. It uses numerous examples to present the coordination of activity in chatting as a high-level individual project, and discusses the question of the extent to which analytical and descriptive categories which have proved their worth in conversational analysis can sensibly be adopted for the description of chat-based communication processes. The theoretical findings are lent empirical support by a case study based on multi-modal data of user activities while chatting.
Description based on publisher supplied metadata and other sources
Keywords: Deutsch; Chatten; Sprachhandeln; Koordination; Konversationsanalyse